2018
DOI: 10.1017/s1365100518000536
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth With Endogenous Economic Institutions

Abstract: Unlike most existing studies on the endogenous institutions, literature on theoretical growth has traditionally considered institutions as exogenous. In this paper, a learn-by-doing-based growth model is adopted and integrated with endogenous institutions to study how economic agents’ incentives engage in institutional improvements or exploit institutional imperfections. From maximization of identical agent utility, the economic growth model includes capital, labor, technology, and institutions. The study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Without a society, there can be no economic activity, and the reverse is that without economic activity, there are no jobs, decent workplaces or money (Ciegis et al, 2015). Thus, for governments, sustainable development represents a real challenge (Li et al, 2020) involving analyzing the cost and benefits of sustainability policies (Islam et al, 2003) and it is more difficult to solve the contradiction that exists between economic growth and environmental and social aspects implied (Hickel, 2019). Government social and economic policies and strategies, as well as environmental laws and regulations, all play a critically important role and impact all three dimensions of sustainability.…”
Section: Societal Sustainable Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Without a society, there can be no economic activity, and the reverse is that without economic activity, there are no jobs, decent workplaces or money (Ciegis et al, 2015). Thus, for governments, sustainable development represents a real challenge (Li et al, 2020) involving analyzing the cost and benefits of sustainability policies (Islam et al, 2003) and it is more difficult to solve the contradiction that exists between economic growth and environmental and social aspects implied (Hickel, 2019). Government social and economic policies and strategies, as well as environmental laws and regulations, all play a critically important role and impact all three dimensions of sustainability.…”
Section: Societal Sustainable Developmentmentioning
confidence: 99%
“…They are constrained to a model of growth that is far from being based on high technology sectors, knowledge-based usage of resources, efficient infrastructures and low dependences on some critical resources (Farooq et al, 2024). To capture the indirect effects of economic growth that can be transmitted to social sustainability, we consider it appropriate to measure it as the quality of public services (PUBLIC QUALITY) public authorities' policy formulation and implementation, and the credibility of the public authorities' commitment to such policies (Li et al, 2020). Institutional quality impacts sustainable development in a positive manner (Azam et al, 2021), especially in lower-middle-income countries than low-income countries.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu (2018) used the survey data of Chinese industrial enterprises from 1998 to 2007 to find that the marginal return on capital of S.O.E.s was 42% lower than that of P.E.s on average, and pointed out that the misallocation of capital among enterprises of different ownership caused by financial repression and policy distortions resulted in a 27.5% reduction in total factor productivity of the Chinese economy. Li et al (2020) found that financial friction is an important factor affecting economic growth, and institutional quality can effectively solve financial friction. However, Liu et al (2021) based on a single department heterogeneous enterprise model based on considering the two great branches of S.O.E.s and P.E.s, the study found that if in the economy there are other aspects of the distortion between departments, to eliminate poor loan interest rate's liberalisation impact on the economy without a definite answer, interest rate liberalisation does not necessarily improve overall productivity and social welfare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of regulation in various sectors of an economy can explain different growth trends across countries (Nicoletti and Scarpetta, 2003;Bassanini and Duval, 2009;Egert 2016;Aghion and Griffith, 2005;De Haan and Parlevliet, 2018), so structural reforms are high on the policy agenda in many OECD economies in the post-pandemic era as a way of boosting recovery and improving economic resilience and long term sustainability (OECD, 2021). Moreover, many scholars and policy makers recognize that good governance and better institutions is a fundamental ingredient of sustained economic development (Kauffman and Kray, 2008;Fernandez and Tamayo, 2017;Li et al, 2020). Differences in economic institutions are the primary source of cross-country differences in economic development and prosperity according to Acemoglu (2004Acemoglu ( , 2005aAcemoglu ( , 2005b.…”
Section: Introductionmentioning
confidence: 99%